FAKTOR-FAKTOR YANG MENENTUKAN MINAT PETANI DALAM BERUSAHATANI SINGKONG (Manihot utilissima) DI DESA REBAQ RINDING KECAMATAN MUARA MUNTAI (Factors Determining Farmer's Interest in Farming Cassava (Manihot utilissima) in Rebaq Rinding Village, Muara Muntai District) - EFFENDI, MIDIANSYAH; JUITA, FIRDA; DINA, NOR (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2023)
Cassava (Manihot utilissima) is the dominant commodity in Rebaq Rinding Village.The land in the village tends to be dry with dry weather and erratic rain , but farmers will continue to carry out cassava farming. The aim of this research is to determine the factors that determine farmers' interest in cassava farming. This research was carried out from March to September 2020 in Rebaq Rinding Village, Muara Muntai District. The location determination method was carried out purposively, the data measurement method used a Likert scale, with a total of 32 respondents. The results of this research show that the factors age (68.25%), education (87.50%), and the role of extension workers (100%) do not determine farmers' interest. Meanwhile, land area (81.25%), experience (93.75%) , number of dependents (87.50%), income (100%), and marketing (100) greatly determine the interest of farmers in Rebaq Rinding Village in cultivating cassava.